ENVIRONMENTAL EDUCATION TRANSFORMATION IN EARLY CHILDHOOD TRHOUGH HORSE RACING AT DOMPU TRIBE - Ihlas, Ihlas; Yufiarti, Yufiarti; Edwita, Edwita (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
This study aims to examine the role of traditional horse racing games in the tribes of the Dompu tribe, Indonesia. This study uses a qualitative approach with ethnographic methods. The subjects of the study were five young jockeys aged 4-8 years and seven horse owners. Data were collected through observation, interviews, documentation and focus group discussion (FGD). Data were analyzed using domain analysis techniques, taxonomic analysis, componential analysis and theme analysis. The results of the study indicate that the transformation of enviromental education in early childhood through horse racing games is done by growing children's concern for the environment and caring for animals, such as horses. During the process of horse racing, children are not permitted to damage nature and hurt animals. Therefore, horse racing becomes a means of enviromental education for children for the sake of the preservation of nature. Horse racing is also one of the most environmentally cared tourist destinations for local people. Another important finding is that the traditional horse racing game in the Dompu tribe has become a medium of transformation of enviromental education of for early childhood. This study informs that the transformation of environmental education can be done since children are aged 4 years through traditional horse racing games. This research can also be a reference for early childhood education practitioners to create a special school for children who have a hobby of riding horses.